solve this problem its urgent
Sorry for blur image
Attachments:
![](https://hi-static.z-dn.net/files/d87/a4c8506ca69577788f3d950cc954e19e.jpg)
Answers
Answered by
6
Answer:
→ (-3)² * (-3)⁻⁶
a⁻ⁿ = 1/aⁿ
→ (-3)² * 1(-3)⁶
→ (-3)²/(-3)⁶
bᵃˣ = (bᵃ)ˣ
→ (-3)²/(-3²)³
→ (-3)²/[(-3)²×(-3)²×(-3)²]
(-3)² cancels from numerator and denominator
→ 1/[(-3)²×(-3)²]
→ 1/(-3²)²
(-3)² = 9 = 3²
→ 1/(3²)²
hence, verified.
Answered by
4
Answer:
Here your answer kookie
Explanation:
Btw writing is tooooo good
Attachments:
![](https://hi-static.z-dn.net/files/d10/7e313ad18af4503e8a21d852f7281906.jpg)
![](https://hi-static.z-dn.net/files/d49/b894d8e0b91679eb4ed9e936dc4ef70e.jpg)
Similar questions